Treatments to maintain the postharvest quality of Cut 'Patumma' (Curcuma alismatifolia 'Chiang Mai Pink') flowers - U. Chanasut (2018)
Cut 'Patumma' flowers normally last 10-15d when placed in clean water. 'Patumma' vase life is generally defined by when the coma bracts have discoloured or stems have wilted. A rapid decrease in water uptake within four days after harvest may trigger the withering of the stem. A preliminary vase life experiment with treatments of a solution containing plant growth regulators, gibberellic acid (GA3) and benzyladenine (BA), delayed the withering and collapsing of stem. A pulsing treatment with 1 mM silver thiosulphate (STS) for less than one hour, increased the number of opened flowers, but had no significant influence on the inflorescence longevity. The chemicals used in this study had no effects either on prolonging the vase life or increasing 'Patumma' flower opening; indeed some treatments actually caused inflorescence stems to collapse earlier.